The Effectiveness of Telemedicine in Managing Catastrophic Disease Emergencies in Remote Areas: Effectiveness of Telemedicine in Managing Catastrophic Disease Emergencies in Remote Areas - Kurniawan, Rudi Erwin (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2024)
Telemedicine has emerged as a promising solution to overcome geographical and logistical barriers in handling emergency cases of catastrophic diseases, especially in remote areas. This study aims to analyze the effectiveness of telemedicine in managing emergencies related to catastrophic diseases by evaluating its impact on response time, patient outcomes, and healthcare accessibility. The methodology employed includes a systematic review of relevant literature, case studies from various remote healthcare centers, and a comparative analysis of conventional emergency responses versus telemedicine-assisted interventions. The findings indicate that telemedicine significantly reduces response times, facilitates early diagnosis, and enhances coordination between primary healthcare providers and specialists. However, challenges such as limited internet connectivity, inadequate infrastructure, and the need for trained personnel remain obstacles to implementation. This study concludes that telemedicine is a viable and effective tool for improving emergency care in remote regions, provided that adequate investment in infrastructure and training is ensured.